2019
DOI: 10.1002/ece3.5219
|View full text |Cite
|
Sign up to set email alerts
|

Yellow perch genetic structure and habitat use among connected habitats in eastern Lake Michigan

Abstract: Maintenance of genetic and phenotypic diversity is widely recognized as an important conservation priority, yet managers often lack basic information about spatial patterns of population structure and its relationship with habitat heterogeneity and species movement within it. To address this knowledge gap, we focused on the economically and ecologically prominent yellow perch (Perca flavescens). In the Lake Michigan basin, yellow perch reside in nearshore Lake Michigan, including drowned river mouths (DRMs)—pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
(95 reference statements)
1
11
0
Order By: Relevance
“…For example, Euclide et al ( 2020 ) detected strong genetic structure in Lake Michigan smallmouth bass across small spatial scales (10–30 km), which often correlated to differences in habitat type rather than geographic distance, and found that gene flow between lake and river sites was low, even though individuals from the two habitat types likely mixed outside of the spawning season. Additionally, Chorak et al ( 2019 ) observed genetic structure in yellow perch populations between Lake Michigan and connected DRM habitats, even though the different populations overlapped during parts of the year. Taken together, our findings and those of past studies suggest that, for some Great Lakes species, distinct tributary and Great Lakes populations may have adapted to different habitat types and historically maintained low levels of gene flow even before the construction of anthropogenic barriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Euclide et al ( 2020 ) detected strong genetic structure in Lake Michigan smallmouth bass across small spatial scales (10–30 km), which often correlated to differences in habitat type rather than geographic distance, and found that gene flow between lake and river sites was low, even though individuals from the two habitat types likely mixed outside of the spawning season. Additionally, Chorak et al ( 2019 ) observed genetic structure in yellow perch populations between Lake Michigan and connected DRM habitats, even though the different populations overlapped during parts of the year. Taken together, our findings and those of past studies suggest that, for some Great Lakes species, distinct tributary and Great Lakes populations may have adapted to different habitat types and historically maintained low levels of gene flow even before the construction of anthropogenic barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Similar variations in life‐history strategies have recently been uncovered in some of our other study species as well. Chorak et al ( 2019 ) and Senegal et al ( 2020 ) both found that in eastern Lake Michigan, yellow perch exhibited multiple life‐history variations, in which some yellow perch were Lake Michigan residents, some were DRM lake residents, and some were Lake Michigan fish that temporarily moved into DRM lakes during the fall. It is therefore possible that prior to dam construction, GL juvenile fish from some or all of our species not only entered the lower Boardman River, as we observed in our study, but also traveled upstream of the current dam site and utilized habitat in Boardman Lake, which is a natural DRM lake, and perhaps further upstream as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yellow Perch (Perca flavescens), and Flathead Catfish (Pylodictis olivaris), all exhibit seasonal movements within Michigan rivers and between drowned river mouth habitats and Lake Michigan (Chorak et al, 2019;Daugherty & Sutton, 2005;DePhilip et al, 2005). While differences in fish detections between June and August likely reflect the seasonal movements of these fishes in the study area, we cannot rule out the possibility that the removal of nearly twice the positive detections for the June sampling event while controlling for contamination contributed to the seasonal differences detected.…”
Section: Differences In Taxa Detections Across Sampling Eventsmentioning
confidence: 95%
“…Drowned river mouth lakes also are important nursery habitat for juvenile lake sturgeon throughout the year (Altenritter et al, 2013). Nevertheless, DRM lakes often become thermally stratified during summer, and dissolved oxygen concentrations can become low in the hypolimnion (Biddanda et al, 2018; Chorak et al, 2019), which has been shown to affect the distribution of fish (Weinke & Biddanda, 2018). For example, juvenile lake sturgeon avoided areas in a DRM lake with low dissolved oxygen concentrations (<4 mg/L; Altenritter et al, 2013), although adults may be less sensitive (Damstra & Galarowicz, 2013).…”
Section: Introductionmentioning
confidence: 99%